Effects of Antihypertensive Drugs on Thyroid Function in Type 2 Diabetes Patients With Euthyroidism - Yang, Lijuan; Sun, Xiuqin; Zhao, Yi; Tao, Hong (Frontiers in Pharmacology, 2022)
Objective: There is little literature about whether antihypertensive drugs would affect thyroid function in patients with euthyroid type 2 diabetes, which was significant in maintaining a proper balance of thyroid function. A retrospective cohort study was conducted to evaluate the influence of antihypertensive drugs on thyroid function in patients with type 2 diabetes with euthyroidism. Design and Methods: The study involved dividing 698 patients with antihypertensive monotherapy into five groups according to the antihypertensive drugs they were treated with. Antihypertensive drugs included in this study were β-blockers, angiotensin-converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARB), and calcium channel blockers (CCB). The clinical data and thyroid function level between or within groups were compared. Multiple logistic regression analysis was conducted to evaluate the association of antihypertensive drugs with thyroid function level. Results: Selective β1- adrenergic receptor blockers treatment was related to thyroid-stimulating hormone (TSH), increasing in patients with diabetes and euthyroidism as shown by multiple logistic regression analysis. The association existed after adjustment for confounding factors. No significant influence on thyroid function was found among other antihypertensive drugs. Conclusion: These data show the TSH-lifting effect of selective β1-adrenergic receptor blockers in patients with type 2 diabetes with euthyroidism.